The Effect of Bentonite and Palm Shell Ash on The Mechanical and Physical Properties of Geopolymer Concrete - Hendronursito, Yusup; Amin, Muhammad; Chambioso, Yugo; Suharto; Marjunus, Roniyus (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2022)
Geopolymer concrete is an alternative to obtaining environmentally friendly mortar by synthesizing materials that contain a lot of aluminum silicate. This study aims to determine the effect of bentonite and palm shell ash composition on geopolymers' physical and mechanical characteristics. All materials are mashed, mixed, and molded with a 5x5x5 cm3 cube. Ten specimens were prepared with bentonite - palm shell ash compositions are 40/45, 45/40, 50/35, 55/30, and 60/25 wt%. Meanwhile, the composition of NaOH, Na2SiO3, superplasticizer and water remained at 1.3, 7.7, 2, and 5 wt%, respectively. Then the samples were dried at room temperature for 24 hrs and heated at 60 °C or 80 °C for 12 hrs. The geopolymer concrete with the best characteristics was obtained with a composition of 40 wt% bentonites and 45 wt% palm shell ash by heating at 80 °C. This specimen has a compressive strength of 11.94 MPa with a density of 2.42 g/cm3, porosity of 8.43%, and absorption of 3.48%. The results have a chemical composition of 55.59% SiO₂, 9.45% Al2O3, and 8.22 Fe2O3 with a dominant quartz phase. Scanning electron microscope photo shows good bonding between particles, and there are no pores formed.